2014
DOI: 10.1128/genomea.01080-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus coagulans GBI-30, 6086, a Widely Used Spore-Forming Probiotic Strain

Abstract: Bacillus coagulans GBI-30, 6086 is a safe strain, already available on the market, and characterized by certified beneficial effects. The draft genome sequence presented here constitutes the first pillar toward the identification of the molecular mechanisms responsible for its positive features and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…coagulans has been reported as safe by the US Food and Drug Administration (FDA) and the European Union Food Safety Authority (EFSA) and is on the Generally Recognized As Safe (GRAS) and Qualified Presumption of Safety (QPS) list [19]. In addition, it was reported that genome sequencing can provide information about the overall characterization of the bacterium, for example with respect to its safety as a food supplement [20]. The B. coagulans GBI-30, 6086 genome was investigated, and it was found that it did not contain any hazardous genes [21].…”
Section: Introductionmentioning
confidence: 99%
“…coagulans has been reported as safe by the US Food and Drug Administration (FDA) and the European Union Food Safety Authority (EFSA) and is on the Generally Recognized As Safe (GRAS) and Qualified Presumption of Safety (QPS) list [19]. In addition, it was reported that genome sequencing can provide information about the overall characterization of the bacterium, for example with respect to its safety as a food supplement [20]. The B. coagulans GBI-30, 6086 genome was investigated, and it was found that it did not contain any hazardous genes [21].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the recent work has confirmed that the genome of B. coagulans contains determinants involved in the adhesion (i.e. fibronectin-and mucus-binding proteins) (Orrù et al 2014). Bidle et al (1993) ever found that surface-associated proteins of B. coagulans are involved in the adhesion.…”
Section: Discussionmentioning
confidence: 93%
“…That was the case of Torrea et al, who found concentrations of nonvolatile amines and phenethylamine in wines from inoculated must were superior to those of the control wine (uninoculated must) [87]. On the other hand, with the concern of strain safety, is interesting to remark on the advances allowed by integrated genome-based assessments of the safety of specific microbial biotypes (e.g., [88,89]). …”
Section: Matrix Evidences Referencementioning
confidence: 99%